Effect of Dietary Flaxseed Oil on Growth Performance and Serum Lipid Profiles in Broilers - Al-Hilali, Ali H. (Pakistan Journal of Nutrition, 2018)
Objective: The present study was conducted to investigate the effect of flaxseed oil supplementation on broiler growth performance and serum lipid profiles. Materials and Methods: Two-hundred broiler chicks (age: 1 day) were randomly allocated to five experimental groups and fed isoenergetic and isonitrogenous diets containing 0, 2.5, 5.0, 7.5, or 10 g kg–1 flaxseed oil for 35 days. Blood was then sampled from the bronchial vein and the serum was isolated to examine serum lipid profiles. Results: Daily flaxseed oil supplementation decreased body weight gain and feed intake, but increased the feed conversion ratio. Flaxseed oil also decreased total cholesterol, triglyceride and very-low-density (VLDL) and low-density lipoprotein (LDL) levels in serum and increased high-density lipoprotein) HDL (levels. Dietary flaxseed oil treatment significantly reduced the weight gain in broilers. Conclusion: Addition of flaxseed oil in broiler diets reduced weight gain, increased feed conversion ratios and improved serum lipid profiles.